Piplartine attenuates the proliferation of hepatocellular carcinoma cells via regulating hsa_circ_100338 expression. (13th April 2020) - Cheng, Xiaoli; Tian, Pan; Zheng, Wengzhong; Yan, Xuetao
Abstract: Researches have pointed that piplartine inhibits the proliferation of hepatocellular carcinoma (HCC) cells, however, the underlying mechanisms has not been well defined. Currently, more and more studies have pointed out that circRNAs can regulate tumor cell proliferation, involve in the tumorigenesis mechanism of various tumors. In this study, we explored whether piplartine may participate in the development of HCC through the regulation of ability of HCC cell proliferation by circRNA. Based on the chip analysis, we selected candidate circRNAs that are highly correlated with HCC. CircRNA expression in OSCC cells treated with piplartine was detected by qRT‐PCR. We found that only the expression of hsa_circ_100338 (circ‐100338) was observably reduced. The expression characteristics of circ‐100338 in HCC cell lines were also verified by qRT‐PCR. Subsequently, whether or notcirc‐100338 can regulate ZEB1 via competitively binding to miR‐141‐3p was determined by the RIP assay and dual luciferase reporter gene assay. The effect of the circ‐100338/miR‐141‐3p/ZEB1 axis on the proliferation of HCC cell was tested by EdU and CCK‐8 assay. Results showed that circ‐100338 expression was observably increased in HCC cell lines. Simultaneously, circ‐100338 can regulate the expression of ZEB1by competitively binding to miR‐141‐3p. Moreover high expression of circ‐100338 can stimulate the proliferation of HCC cells. Our current study revealed that circ‐100338 played as a ceRNA in promoting the progression of HCC by sponging miR‐141‐3p, while piplartine can participate in the development of HCC by inhibiting the expression of circ‐100338. Abstract : Hsa_circ_100338 was upregulated in piplartine treated hepatocellular carcinoma cells. Dual luciferase reporter gene assay and RIP assay showed that circ‐100338 can regulate ZEB1 expression by competitively bind to miR‐141‐3p.